Gun Laws and Crime: An Empirical Assessment - Matti Viren (Aboa Centre for Economics (ACE), 2012)
This paper deals with the effect of gun laws on crime. Several empirical analyses are carried to investigate the relationship between five different crime rates and alternative law variables. The tests are based on cross-section data from US sates. Three different law variables are used in the analysis, together with a set of control variables for income, poverty, unemployment and ethnic background of the population. Empirical analysis does not lend support to the notion that crime laws would affect the crime rates. The results seem to be the same for all five crime categories that are analyzed in the paper.
Keywords: K42; 330; crime; gun laws; crime data